2017
DOI: 10.6000/1927-5129.2017.13.22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Bio-Pesticides against Major Sucking Pests on Brinjal under Field Conditions

Abstract: A field study was carried out during 2015 at the experimental area of Entomology Section, Agriculture Research Institute, (ARI) Tando Jam to examine the efficacy of different bio-pesticides against major sucking pests on brinjal under field conditions. Four treatments with three replications were applied. The treatments were: T1=Neem (Azadirachta indica), T2= Tobacco (Nicotiana tabacum), T3= Datura (Datura stramonium) and T4=Control (untreated). Three insect pests were found infesting brinjal including white f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Similarly, numerous other neem-based products showed effectiveness of Myzus persicae on several host plants (Akbar et al 2010). The neem extract was extremely effective to control jassid, whitefly, aphid, and mites on brinjal (Ali et al 2017).…”
Section: Efficiency Of the Biopesticides Against Tetranychus Urticaementioning
confidence: 99%
“…Similarly, numerous other neem-based products showed effectiveness of Myzus persicae on several host plants (Akbar et al 2010). The neem extract was extremely effective to control jassid, whitefly, aphid, and mites on brinjal (Ali et al 2017).…”
Section: Efficiency Of the Biopesticides Against Tetranychus Urticaementioning
confidence: 99%
“…The higher effect may be due to the application of concentrated bioactive compounds, the experimental setting, and the crop involved. Similarly, Ali et al [46] proved that neem extract was potent against whiteflies, reporting up to 82.60% reduction in the whitefly population in brinjal at 50% w/v two weeks after application. This was higher than our findings, with 58.1% reduction at 10% w/v two weeks after the first spray, and the higher effect could be due to the higher concentration applied in their studies.…”
Section: Discussionmentioning
confidence: 86%
“…The mixture of acetone extract of crown flower and ethanolic extract of neem seed in the ratio 3:1 shows higher insecticidal effect against spiraling white fly compared to other combinations formulated in their study (Alim et al, 2017). Ali et al (2017) reported neem seed extract is the most effective insecticide against sucking insect pests, compared to other plant extracts used in their research work.…”
Section: Neem Based Pesticidesmentioning
confidence: 90%